PERLINDUNGAN HUKUM TERHADAP PEMEGANG TANAH HAK ADAT - Benyamin Tomas Setiawan; Endang Pandamdari (Reformasi Hukum Trisakti, 2022)
As Lahat Regency's Indigenous Peoples, the Dalian have inherited land from their ancestors. The land belongs to the late Maijah binti Jamun, and according to the customary certificate with the number 038/P/TS/2018/1994, she had the status of having customary land rights. By entering into an agreement and a contract with the late Maijah Binti Jamun, Arta Prigel has control over the customary land that is owned by Dalian as the plaintiff and the land certificate has been issued as a Cultivation Right. However, the agreement was not paid for until a lawsuit was filed by Dalian as well as one of the heirs. The issue is whether DALIAN as successors' possession of land with customary ownership rights complies with national land law according to certificate of traditional land rights 038/P/TS/1994. Based on SUPREME COURT DECISION 3173 K/Pdt/2019 by PT. Artha Prigel, how is the legal protection of owners of traditional property rights in connection to land tenure. This style of legal study is descriptive normative. Secondary data is what was used.